Imaging Embryonic Stem Cell Dynamics Using Quantitative 3-D Digital Holographic Microscopy - A. Anand; V. K. Chhaniwal; B. Javidi (IEEE Photonics Journal, 2011)
Embryonic stem cells are very important for the development of cell-based therapeutic strategies. Since stem cell colonies are nonpigmented and relatively transparent, they do not produce appreciable variation to the amplitude of probe electromagnetic radiation passing through them, necessitating the use of phase contrast imaging techniques for studying them. Here, we used digital holographic interferometric microscopy (DHIM) to observe temporal and spatial evolution of stem cell colonies. Three-dimensional or whole field imaging has yielded important quantitative information about their progression from single cell to colonies. Information on the time and spatial evolution of optical volume and path length change will be an important tool for biologists working in the area of stem cells and their development.